2022
DOI: 10.1093/rheumatology/keac608
|View full text |Cite
|
Sign up to set email alerts
|

Anti-rituximab antibodies demonstrate neutralizing capacity, associate with lower circulating drug levels and earlier relapse in lupus

Abstract: Objectives High rates of anti-drug antibodies (ADA) to rituximab have been demonstrated in patients undergoing treatment for systemic lupus erythematosus (SLE). However, little is known with regards to their long-term dynamics, impact on drug kinetics and subsequent implications for treatment response. In this study, we aimed to evaluate ADA persistence over time, impact on circulating drug levels, assess clinical outcomes and whether they are capable of neutralising rituximab. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…In the present study, we found no association between the frequently observed anti-rituximab antidrug antibodies and response to treatment. However, anti-rituximab antidrug antibodies have been shown to be frequently present in other diseases, such as multiple sclerosis, and to be associated with relapse in lupus . The importance of transient antidrug antibodies remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found no association between the frequently observed anti-rituximab antidrug antibodies and response to treatment. However, anti-rituximab antidrug antibodies have been shown to be frequently present in other diseases, such as multiple sclerosis, and to be associated with relapse in lupus . The importance of transient antidrug antibodies remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the number and frequency of rituximab injections are likely to affect the formation of ARAs in MS but not in lymphoma, leukemia, or Crohn’s disease ( 23 , 28 , 29 ). Moreover, ARAs development was associated with reduced B-cell depletion in rituximab-treated patients in MS, but this association is controversial in SLE ( 23 , 30 , 31 ). Therefore, the factors inducing ARAs formation in nodopathy should be deeply explored.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we assumed that the poor outcome of anti-NF155-positive patients who did not respond well to rituximab might be attributed to the occurrence of ARAs. Besides, ARAs in patients with SLE can neutralize drug level and counteract the cytotoxicity of rituximab in vitro ( 31 ). In nodopathy, the functional assessment of ARAs and drug level are worthy of deep exploration and research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 153 , 154 , 156 , 157 It has also been found for IL-6 receptor inhibitors: tocilizumab and sarilumab 158 , 159 and, most recently, rituximab. 160 …”
Section: Clinical Factors Predicting Drug Responsementioning
confidence: 99%